Exclusive breastfeeding and its effect on growth of Malawian infants: results from a cross-sectional study - Kuchenbecker, J.; Jordan, I.; Reinbott, A.; Herrmann, J.; Jeremias, T.; Kennedy, G.; Muehlhoff, E.; Mtimuni, B.; Krawinkel, M.B. (Informa UK Limited, 2015)
Abstract Background: